Organic geochemical characteristics of Jurassic Yan ’an Formation source rock in Pengyang area of southwestern Ordos basin - Yaling Zhu; Yaling Zhu; Wenmei Tan; Lianfu Hai; Lianfu Hai; Caixia Mu; Caixia Mu; Kun Wang; Mengyuan Li (Frontiers in Earth Science)
The Jurassic Yan ’an Formation in the southwestern margin of Ordos Basin has developed many sets of coal-associated and non-associated mudstone as well as oil shale. Different analytical methods including total organic carbon (TOC), Rock-Eval pyrolysis, and conventional biomarker analyses were applied on the mudstone, the coal and the oil shale extracts to unravel their organic geochemical characteristics and the paleo depositional environment. Results reveal that all the source rock samples are immature to mature with good petroleum generation potentials. The redox environment is generally reducing. The organic matter input is mainly terrestrial higher plants. The low Ga/C30 hopane ratio of all the samples indicate the low salinity of the paleo-water column. The oil shale samples show much higher thermal maturity than the coals and mudstones as indicated by the higher C31 homohopane isomerization indexes, C32 homohopane isomerization indexes and the C29 sterane ααα20S/(S + R) ratios. The depositional environment of the oil shale is more reduced compared to the coals and mudstones as can be reflected by the low oxygen index and the higher C35 hopane/(C31-C35 homohopanes) ratios. Thus, the oil shale layers should be the target of the next exploration and development. And the Oil shale and coal can be exploited simultaneously in Pengyang area.